Odpowiedzi

2009-09-21T18:22:17+02:00
A)
{-y = 7 - 4x /*(-1)
{5x+y=11

{y=4x-7
{5x+4x-7=11

{y=4x-7
{9x=18

{y=4*2-7
{x=2

{y=1
{x=2

b)
{1/2x=2y-5 /*2
{-1/2y=4,5-3x /*(-2)

{x=4y-10
{y=-9+6(4y-10)

{x=4y-10
{y=-9+24y-60

{x=4y-10
{-23y=-69

{x=4y-10
{y=3

{x=12-10
{y=3

{x=2
(y=3
2009-09-21T18:23:15+02:00
A)4x-y=7
5x+y=11

9x=18 /:9
x=2
Obliczamy y:
4*2-y=7
8-y=7
-y=7-8
-y=-1 / * (-1)
y=1

b)1/2x-2y=-5
3x-1/2y=4,5 /* (-4)

1/2x-2y=-5
-12x+2y=-18

-11 1/2x = -22

-23/2 x= -22 / *(-2/23)
x= 44/23
x= 1 21/23

3x- 1/2y = 4,5
3* 44/23 - 1/2y= 4,5
132/23 - 1/2y = 4,5
5 17/23 -1/2y = 4,5
-1/2y = 4,5 - 5 17/23
-1/2y = 45/10 - 132/23
-1/2y = 1035/230 - 1320/230
-1/2y = -285/230 / *(-2)
y= 570/230
y= 2 10/230
y= 2 1/23

Co do drugiego wyniku nie jestem pewien... Sprawdź sobie ;)


2009-09-21T18:55:32+02:00
A) 4x-y=7
5x+y=11

9x=18/podzielić przez 9
x=2

4*2-y=7
5*2+y=11

-y=7-8/ podzielić przez-1
y=11-10

y=1
x=2

b)
1/2x-2y=-5/*2
3x-1/2y= 4,5/*(-2)

x=4y-10
y=-9+6 (4y -10)

x=4y*10
-23y=-69/podzielić (-23)

x=4y*10
y=3

x=12-10
y=3

x=2
y=3